Can a Self-Management Education Program for Patients with Chronic Obstructive Pulmonary Disease Improve Quality of Life ?. Issue 5 (2011) - Labrecque, Manon; Rabhi, Khalil; Laurin, Catherine; Favreau, Helene; Moullec, Gregory; Lavoie, Kim; Julien, Marcel
Abstract : OBJECTIVE: To assess the effects of a self-management program on health-related quality of life (HRQoL) and morbidity commonly associated with chronic obstructive pulmonary disease (COPD). METHODS: A total of 57 outpatients with stable COPD received four weeks of self-management education, while 45 patients received usual care. Patients were evaluated at baseline, at three months and one year following the educational intervention. The primary outcome variable was HRQoL measured by the St George's Respiratory Questionnaire (SGRQ). The secondary outcome variables were number of emergency room visits and hospitalizations for exacerbation. RESULTS: The intervention group's HRQoL improved significantly at three months (total score A=−5.0 [P=0.006]) and 12 months (total score A=−6.7 [P<0.001]), as evidenced by decreased scores on the SGRQ. In contrast, the SGRQ scores increased significantly in the control group at three months (total score A=+3.7 [P= 0.022]) and 12 months (total score A=+3.4 [P=0.032]). Global impact appeared to be responsible for the change in the intervention group. Moreover, in the intervention group, the number of hospitalizations dropped from 0.7/person/year to 0.3/person/year (P=0.017), and emergency room visits dropped from 1.1 person/year to 0.2/person/year (P=0.002), while subjects in the control group did not experience any significant decreases in these parameters. CONCLUSIONS: A planned education program improved HRQoL while decreasing the number of emergency room visits and hospitalizations in patients with stable COPD; this improvement persisted at 12 months.